The Effect of ENSO on Upwelling Events in Bengkulu City Waters (Case Study: El Nino 2023) - silaban, Angeli; Johan, Septi; Lizalidiawati, Lizalidiawati (Jurnal Ilmiah Sains, 2025)
One of the areas affected by the ENSO phenomenon is the waters of Kota Bengkulu. The 2023 El Nino event was categorized as strong, making it essential to understand its impact on upwelling in the waters of Kota Bengkulu. The objective of this study is to examine the influence of the 2023 El Nino on the upwelling phenomenon in the waters of Kota Bengkulu. The data used in this study were obtained from Marine Copernicus and NOAA, consisting of monthly averages over a two-year period (2022–2024). The research method applied is descriptive and quantitative. The descriptive method illustrates the 2D distribution of Sea Surface Temperature (SST), Sea Surface Height (SSH), and Chlorophyll-a during the 2023 El Nino event. Meanwhile, the quantitative method analyzes the values of SST, SSH, and Chlorophyll-a corresponding to the period of the El Nino event. The results indicate that the strong El Nino of 2023 caused a significant decrease in sea surface temperature, reaching 26.9°C in September 2023. This decline in SST was attributed to upwelling in the waters of Kota Bengkulu, driven by the Southeast Monsoon coinciding with the strong El Nino event, which had an ONI value of 1.8°C. The occurrence of upwelling was also indicated by a lower SSH in October 2023, recorded at 0.2 m. Additionally, Chlorophyll-a concentration increased in October 2023, reaching 16.2 mg m⁻³, following the decrease in SST in September 2023. The peak of the 2023 El Nino in October further intensified the upwelling event that year. Keywords: chlorophyll-a; ENSO; sea surface height; sea surface temperature; upwelling